Physiological basis of the genetic progress on corn (Zea mays L.) cultivars from the PRM. - Bolaños, Jorge (2016)
The germplasm development has been one of the most outstanding achievements of the PRM (Regional Corn Program). The objective of this test was to understand the physiological basis of genetic gain in the most important corn cultivars from the PRM, by determining the parameters of important physiological, phenological and morphological standards on the elabora-tion of yields. Nine cultivars (5 hybrids and 4 open-pollinated ed varieties OPV's) were evaluated in a Complete Ran-domized block design with 3 replications across 11 diverse environments of the region. The hybrids consistently Clot yielded the OPV' s by 1.0-1.5 t/ha across all the environments. The basis for such differences seemed to rely on the higher daily ear growth-rate of the hybrids (2.7 g/day) than of the OPV's (2.3 g/day). The final yield of each cultivar is the product ofthis efficiency by the grain-filling days. Differences in yield among hybrids and OPV's, as germp1asm groups, depended on the duration of grain-filling and not on the growth-rate of ears. The CB- HS7 and HB-85 hybrids took 6 more days of grain-filling than P- 8916 and H-5. The Sint. Sequia, within the OPV' s, last 3 more days of grain-filling than the others. A large negative relationship was detected between grain-filling lenght and maturity, suggesting that the earlier the genotype, lesser time is invested in producing leaves and more in grain-filling. Consistent with this data, hybrids have a higher harvest index than OPV's. It also suggest that an effective mechanism to increase yield is to extend the grain-filling periodo Current breeding schemes should consider these selec-tion criteria.